2002
DOI: 10.1177/0192513x02023003003
|View full text |Cite
|
Sign up to set email alerts
|

Child Functioning and Caregiver Well-being in Families of Children with Emotional Disorders

Abstract: Early et al. / CHILD FUNCTIONING, CAREGIVER WELL-BEINGResearchers and practitioners concerned about children with emotional disorders and their families often try to understand the relationship between a child's condition and family functioning. Does some aspect of the caregiver affect the child's emotional and behavioral difficulties? Does the strain of caring for a child with such difficulties have an impact on parents? Does each affect the other in some reciprocal fashion? Previous research has often been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 14 publications
3
27
0
Order By: Relevance
“…In the process of deinstitutionalization of persons with intellectual disabilities, parents of children with ASD are a key factor in improving the functioning of their children (Early et al 2002;Turnbull et al 2004). According to the latest guidelines on therapy and rehabilitation of children with ASD (daily lifetime therapy), and from the standpoint of harmony in all life aspects of the child, parents assume a very important role in care and rearing (Welch 1997) and therefore they must have an adequate quality of life (Yau and Li-Tsang 1999).…”
mentioning
confidence: 99%
“…In the process of deinstitutionalization of persons with intellectual disabilities, parents of children with ASD are a key factor in improving the functioning of their children (Early et al 2002;Turnbull et al 2004). According to the latest guidelines on therapy and rehabilitation of children with ASD (daily lifetime therapy), and from the standpoint of harmony in all life aspects of the child, parents assume a very important role in care and rearing (Welch 1997) and therefore they must have an adequate quality of life (Yau and Li-Tsang 1999).…”
mentioning
confidence: 99%
“…The emotional and coping reactions of parents or caregivers to their child's MH problems and diagnoses are of interest because these are tied to parent's own wellbeing as individuals, family relationships and children's outcomes (Early et al 2002;Oppenheim et al 2007). For instance, Oppenheim et al (2007) who studied the impact of ''diagnostic resolution'' among parents of children with autism spectrum disorders, found that mothers classified as resolved (meaning they have incorporated the experience of the child's diagnosis and reoriented their expectations) were also more sensitive to their children, and their children were more responsive to them.…”
Section: Parents' Reactions To Their Child's Mh Problems and Psychiatmentioning
confidence: 99%
“…In addition, existing research in child mental health services reflects the fact that the primary caregiving role tends to fall primarily to mothers [4][5][6]. Consequently, these mothers appear to be at higher risk for stress related difficulties which, in turn, are associated with negative child behavioral profiles in these families [4,7].…”
Section: Introductionmentioning
confidence: 99%